Periodontal ligament‐derived cells for periodontal regeneration in animal models: a systematic review. (26th June 2014) - Bright, R.; Hynes, K.; Gronthos, S.; Bartold, P. M.
Abstract : Background and Objective: Implantation of periodontal ligament stem cells is emerging as a potential periodontal regenerative procedure. This systematic review considers the evidence from animal models investigating the use of periodontal ligament stem cells for successful periodontal regeneration. Material and Methods: PubMed, Embase, MEDLINE and Google Scholar were searched to December 2013 for quantitative studies examining the outcome of implanting periodontal ligament stem cells into experimental periodontal defects in animals. Inclusion criteria were: implantation of periodontal ligament stem cells into surgically created periodontal defects for periodontal regeneration; animal models only; source of cells either human or animal; and published in English. We followed the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Results: From the literature search, 43 studies met the inclusion criteria. A wide variety of surgical defects were created in four species of animal (dog, rat, pig and sheep). Owing to wide variability in defect type, cell source and cell scaffold, no meta‐analysis was possible. Outcome measures included new bone, new cementum and new connective tissue formation. In 70.5% of the results, statistically significant improvements of these measures was recorded. Conclusion: These results are notable in that they indicate that irrespective of the defect type and animal model used, periodontal ligament stem cell implantation can be expected to result in a beneficial outcome for periodontal regeneration. It is recommended that there is sufficient evidence from preclinical animal studies to warrant moving to human studies to examine the efficacy, safety, feasibility (autologous vs. allogeneic transplantation) and delivery of periodontal ligament stem cells for periodontal regeneration.